Kelarutan Lignin Kayu Cepat Tumbuh dalam Ekstraksi Alkali - Deded Sarip Nawawi; Adesna Fatrawana; Wasrin Syafii (Faculty of Forestry Universitas Gadjah Mada, 2021)
The dissolution of wood lignin in the alkali solution were analyzed for two fast growing species, sengon (Paraserianthes falcataria) dan leda (Eucalyptus deglupta). Wood samples were extracted in 1% sodium hydroxide solution in cold and hot temperatures for 24 and 1 h, respectively. Extractable substances content, permanganate consumption (expressed as assumed lignin content) were analyzed from the filtrates, lignin content and diastereomeric of β-O-4 structure were analyzed from the wood residue after alkali extraction. The extracted substances from both of wood in hot alkali was higher than in cold alkali solution, although the time of cold alkali extraction was much longer that hot alkali extraction. Assumed lignin content in the extract was quite high in both samples which were 34.4-42.9% and 35.5-39.8% including 2,15-2,29% dan 1,04-1,32% of lignin for cold and hot alkali extraction, respectively. The changes in stereo isomeric form, erythro and threo, of β-O-4 structure of lignin in wood residue indicated that partial depolimerization of lignin was takec place during alkali treatment.